Annual reproductive cycle and condition index of Mactra corallina (Mollusca: Bivalvia) from the north coast of Tunisia. Issue 1 (2nd January 2019) - Chetoui, Imene; Telahigue, Khaoula; Bejaoui, Safa; Rabeh, Imen; Ghribi, Feriel; Denis, Françoise; ElCafsi, M'Hamed
ABSTRACT: This work aims to examine the reproductive cycle of the bivalve Mactra corallina inhabiting the Gulf of Tunis (Tunisia). Histological analysis indicated that the reproductive cycle is composed of six stages and was synchronous between sexes. Gonadal development began in January. From April to July, an increase in temperature (from 16 to 28°C) and a rise in chlorophyll a (from 3.25 to 6.35 mg/L) marked the period of sexual maturity in both sexes, which was also confirmed by an elevation in condition index (CI). Partial spawning started in April for males and in May for females, peaking in late summer indicating a prolonged reproductive period. The reproductive cycle of M . corallina finished with an inactive stage during autumn. From the total number of animals used in this study, we identified 104 females (52%) and 96 males (48%) corresponding to a sex ratio 1:0.92 that did not differ significantly from a 1:1 ratio.